Efektivitas Penerapan Model Pembelajaran Kooperatif Quick on The Draw - Wayan Mahardika Prasetya Wiratama (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
This research is expected to provide an overview and information on the effectiveness of the ‘Quick on the Draw’ cooperative learning model implementation, so that it can be used as a reference material and develop it in a vocational high school study. This research is a classroom action research, aiming to improve the quality or solving problems occurring in a subject group that is researched and observed as a level of success or impact of his actions. The effectiveness of the model is assessed by student activity, student learning outcomes, and student response to the use of the model. The total score of the student activity observation is 87.5% (85% < RA ≤ 100%) in ‘very active’ category. The percentage of students that are collectively completed is 100%, which means that the criteria for the effectiveness of learning devices are met. The interval of the student responses received from the average from student response poll became the class response, where the response of this class is at the range of 3.2 (͞R ≥ 3), meaning the average of overall response is positive and meet the criteria of the learning device effectiveness. The use of this learning model is expected to address the problems often faced by both teachers and students.